2021
DOI: 10.1093/heapro/daab103
|View full text |Cite
|
Sign up to set email alerts
|

eHealth literacy during the COVID-19 pandemic: seeking, sharing, suspicion amongst older and younger UK populations

Abstract: Summary The containment of infectious diseases is most successful when at-risk populations have a high level of relevant health literacy (HL). To achieve this both literacy needs and patterns of knowledge sharing must be understood within the context of the disease being studied. It is also important to understand these processes from both offline (HL) and online (eHL) perspectives and amongst demographics with access to different types of information and social capital, and who have different l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Medical information from governmental and medical authority sources is generally considered accurate and trustworthy, and Swedish society is often characterized by a relatively strong trust in governmental agencies [ 42 ]. However, contrary to our results, Sykes et al described scepticism towards governmental COVID-19 information among their participants [ 26 ]. Prior studies have indicated an association between low health literacy and low trust in information from governmental and medical webpages, although analysis of our results did not reveal any such distinction between groups [ 43 , 44 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Medical information from governmental and medical authority sources is generally considered accurate and trustworthy, and Swedish society is often characterized by a relatively strong trust in governmental agencies [ 42 ]. However, contrary to our results, Sykes et al described scepticism towards governmental COVID-19 information among their participants [ 26 ]. Prior studies have indicated an association between low health literacy and low trust in information from governmental and medical webpages, although analysis of our results did not reveal any such distinction between groups [ 43 , 44 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, a recent qualitative article by Sykes et al described problems with making sense of COVID-19 information because of the general knowledge gap, and the large volume and conflicting nature of the information. In agreement with our findings, Sykes et al also described online COVID-19 information as having a negative impact on the emotions of participants [ 26 ]. Further, the COVID-19 disease itself has been shown to negatively influence the mental health of world citizens, causing anxiety, stress, and depression, and the surrounding infodemic has been described as fueling this effect [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…, 2021; Chen et al. , 2021; Gerosa et al , 2021; Mohammed et al , 2021; Savolainen, 2021; Thomas et al , 2021; Wang et al , 2021) and coronavirus health literacy (Bray et al , 2021; Okan et al , 2020; Sykes et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%